Peran Suasana Hati, Harga Diri dan Sikap Tentang Uang Dalam Mempengaruhi Perilaku Pembelian Kompulsif : Studi Empiris Pada Mahasiswa di Kota Semarang - Kemal Budi Mulyono, Rusdarti, Ubaedul Mustofa (Universitas PGRI Madiun, 2019)
Young people often have fast and underdeveloped decisions, one of which is irrational consumption activities such as compulsive purchases. Some research shows the occurrence of compulsive buying behavior, one of which is due to psychological factors. This study aims to reveal how moods, self-esteem, and attitudes about student money can influence compulsive buying behavior. The data in the study was taken through a measurement scale questionnaire on public or private students in an incidental way to 100 students in the city of Semarang, then with Warp PLS based inferential statistics. From the results of the study showed that mood, self-esteem, a positive effect on compulsive purchases, attitudes about money while negatively affecting compulsive purchases. The implications of this research are psychological factors, it should be controlled through student learning maturity towards personal behavior.